Analisis Faktor-Faktor yang Mempengaruhi Minat Belajar Siswa/Siswi SDN 101823 Bekala Desa Namobintang - Misbah Sihotang; Siti Rahmania; Najda Arija Azukma; Noviva Sihite; Sori Monang An Nadwi (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Learning is an interactive process from there sultof the activities of educators and students in a particular learning environment. In learning the teacher plays a very important role indesigning, implementing and evaluating learning so that each learning design can be realizd properly, then every educator needs to have the ability to design learning well and arouse students interest in learning. Interest is the basic an dimpetus for someone to do what they want if they want to achieve the expected goals. Interest is a convincing foundation for the success of a learning process. Students who have an interest in an object will tend to give greater attention to the material they are studying. Teacher need to arouse students interest in learning so that they canbe excited to receive lessons, make students aware to be directly involved in learning, learn with funand be abietouse various methods of technical strategies and fun learning approaches Keywords: Students, Learning, an Interestin Learning